Employing an Unsaturated Th4+ Site in a Porous Thorium–Organic Framework for Kr/Xe Uptake and Separation. Issue 20 (20th April 2018) - Wang, Yanlong; Liu, Wei; Bai, Zhuanling; Zheng, Tao; Silver, Mark A.; Li, Yuxiang; Wang, Yaxing; Wang, Xia; Diwu, Juan; Chai, Zhifang; Wang, Shuao
Abstract: Actinide based metal–organic frameworks (MOFs) are unique not only because compared to the transition‐metal and lanthanide systems they are substantially less explored, but also owing to the uniqueness of actinide ions in bonding and coordination. Now a 3D thorium–organic framework (SCU‐11 ) contains a series of cages with an effective size of ca. 21×24 Å. Th 4+ inSCU‐11 is 10‐coordinate with a bicapped square prism coordination geometry, which has never been documented for any metal cation complexes. The bicapped position is occupied by two coordinated water molecules that can be removed to afford a very unique open Th 4+ site, confirmed by X‐ray diffraction, color change, thermogravimetry, and spectroscopy. The degassed phase (SCU‐11‐A ) exhibits a Brunauer–Emmett–Teller surface area of 1272 m 2  g −1, one of the highest values among reported actinide materials, enabling it to sufficiently retain water vapor, Kr, and Xe with uptake capacities of 234 cm 3  g −1, 0.77 mmol g −1, 3.17 mmol g −1, respectively, and a Xe/Kr selectivity of 5.7. Abstract : A 3D porous thorium framework has a new coordination geometry for a 10‐coordinate metal ion: bicapped tetragonal prism. The framework (SCU‐11 ) is also one of the most porous actinide materials reported and features a unique open Th 4+ site after activation, leading to superior water vapor and Xe/Kr uptake and separation.